Acute spontaneous extraconal hematic cyst of the orbit - Ali, Hala M. Nassim (Elsevier, 2010)
A 49 year old man presented with one day history of mild right eye pain and proptosis. There was no definite history of trauma. On examination there was limitation of movement in all directions of gaze and 6 mm proptosis of his right eye. CT scan showed extraconal lesion compressing the optic nerve and inferior rectus muscle. Right inferior conjunctival fornix based approach was performed with lateral canthotomy and inferior cantholysis and exploration revealed a cyst containing blood which was removed.